FYR Macedonia Policy-Based Guarantee : Supporting the Development Agenda and Strengthening Access to Capital Markets - Najdov, Evgenij (World Bank, Washington, DC, 2014)
The ongoing global economic turmoil is seriously impeding client countries access to capital markets, with relatively little regard for the fundamentals of the countries involved. Growing risk aversion among investors has triggered a flight-to-quality that is affecting all but the safest assets (AAA-rated). Small, open, and developing economies in Europe and Central Asia, including FYR Macedonia, are being exceptionally hurt. Despite its history of prudent macroeconomic policies and progress on structural reforms, FYR Macedonia s access to capital markets has been virtually closed or available only on very unfavorable terms. Policy-Based Guarantees (PBG) help well-performing clients with a track record of macro stability and structural reforms mitigate market access risks while advancing a country s development policy dialogue. PBGs also have the added benefit of catalyzing private capital flows by alleviating critical risks. The PBG extended by the World Bank to FYR Macedonia ensured the country s access to markets in a virtually closed market environment and at highly competitive terms.